Plastic Polymers and Antibiotic Resistance in an Antarctic Environment (Ross Sea): Are We Revealing the Tip of an Iceberg? - Gabriella Caruso; Maurizio Azzaro; Ombretta Dell’Acqua; Maria Papale; Angelina Lo Giudice; Pasqualina Laganà (Microorganisms, 2024)
Microbial colonization of plastic polymers in Antarctic environments is an under-investigated issue. While several studies are documenting the spread of plastic pollution in the Ross Sea, whether the formation of a plastisphere (namely the complex microbial assemblage colonizing plastics) may favor the spread of antibiotic-resistant bacteria (ARB) in this marine environment is unknown yet. A colonization experiment was performed in this ecosystem, aiming at exploring the potential role of plastic polymers as a reservoir of antibiotic resistance. To this end, the biofilm-producing activity and the antibiotic susceptibility profiles of bacterial strains isolated from biofilms colonizing submerged polyvinylchloride and polyethylene panels were screened. The colonization experiment was carried out at two different sites of the Ross Sea, namely Road Bay and Tethys Bay. Most of bacterial isolates were able to produce biofilm; several multidrug resistances were detected in the bacterial members of biofilms associated to PVC and PE (also named as the plastisphere), as well as in the bacterial strains isolated from the surrounding water. The lowest percentage of ARB was found in the PE-associated plastisphere from the not-impacted (control) Punta Stocchino station, whereas the highest one was detected in the PVC-associated plastisphere from the Tethys Bay station. However, no selective enrichment of ARB in relation to the study sites or to either type of plastic material was observed, suggesting that resistance to antibiotics was a generalized widespread phenomenon. Resistance against to all the three classes of antibiotics assayed in this study (i.e., cell wall antibiotics, nucleic acids, and protein synthesis inhibitors) was observed. The high percentage of bacterial isolates showing resistance in remote environments like Antarctic ones, suffering increasing anthropic pressure, points out an emerging threat with a potential pathogenic risk that needs further deepening studies.